A pragmatic approach to economic development - Basch, Antonín. (New York : Vantage Press, 1970)
This book is about economic and social condition of the less developed countries and to promote their economic development.
Includes bibliographical references.
oo 19/9/18
Loans
Keywords: Economic development; Economic assistance